A Rare Complication of Poorly Controlled Diabetes Mellitus: Testicular Necrosis - Hota, Parthasarathi (Recent Developments in Medicine and Medical Research Vol. 6, 2021)
A 45-year-old male patient with diabetes mellitus was diagnosed with testicular necrosis in this case. Past history suggestive of diabetes with very irregular medication. For three weeks, the patient had gradually increasing right testicular enlargement. Ultrasonography revealed an abscess with no vascularity in the right testis. The right orchiectomy was completed. Testicular necrosis was confirmed by histopathology. Testicular necrosis is a common complication after torsion which leads to orchiectomy. In those cases, patients present with acute onset scrotal pain, which is usually unilateral. On examination, the testis is acutely tender, with red and angry-looking skin overlying it. Urinary tract infections and epididymo-orchitis are common in diabetic patients. Patients present with testicular pain, fever, leucocytosis, and other symptoms. However, testicular necrosis is extremely uncommon. Retinopathy, nephropathy, and neuropathy are long-term complications of diabetes mellitus. Patients with all forms of diabetes of sufficient duration, including insulin-dependent diabetes mellitus and non-insulin-dependent diabetes mellitus, are vulnerable to these complications, which cause serious morbidity. Diabetes mellitus can cause testicular necrosis, which is a very rare complication. An internet search turned up no articles about testicular necrosis as a diabetes complication. For the first time, a case of unilateral testicular necrosis as a complication of diabetes mellitus is presented. This unusual complication was most likely caused by accelerated microangiopathy combined with poor blood glucose control.